Inclusion of slack bus in Newton Raphson load flow study - Kabir, Shahriar Mahmud Lutful; Chowdhury, Abdul Hasib; Rahman, Dr. Md. Mosaddequr Abdur; Alam, Jahangir (© 2014 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 8th International Conference on Electrical and Computer Engineering, ICECE 2014; Pan Pacific Sonargaon DhakaDhaka; Bangladesh; 20 December 2014 through 22 December 2014 [© 2014 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICECE.2014.7026900